The brain in chronic insomnia and anxiety disorder: a combined structural and functional fMRI study - Xu, Minghe; Li, Bo; Wang, Shuang; Chen, Chunlian; Liu, Zhe; Ji, Yuqing; Liu, Kai; Niu, Yujun (Frontiers in Psychiatry, 2024)
Background: Chronic insomnia disorder (CID) is usually associated with Generalized Anxiety Disorder (GAD), which may change brain structure and function. However, the possible brain markers, imaging characteristics, and pathophysiology are unknown. Objective: To look at the probable brain markers, imaging characteristics, and pathogenesis of CID in combination with GAD.The lower GMV in the cerebellum could be interpreted as an imaging characteristic of CID. Reduced GMV in the insula, as well as aberrant function in the cingulate gyrus and prefrontal lobe, may contribute to the pathophysiology of CID and GAD. Abnormal function in the postcentral gyrus and angular gyrus may be associated with patients' clinical complaints.